Peningkatan hasil belajar dalam pembelajaran tolak peluru melalui pendekatan metode bermain bola karet pada siswa kelas VI SDN. 04 Nanggalo Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan - Eliwardi Eliwardi (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2018)
The purpose of this study is to determine the improvement of learning outcomes through the approach of the method of playing rubber ball in the learning of bullets in students. This research is a Classroom Action Research. The sample from the study was 24 people. The results showed an increase in the cycle, I and cycle II. So it can be concluded the method of playing rubber ball can improve the results of bullet's dumb bullets on students.